The Effect of Problem -Solving Strategy on Concentration of Attention shot put performance of physical education Students at Yarmouk University - Nezar "Mohammed Khiar" Al-luwaici (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: The study aimed to identify the effect of the problem-solving strategy on focusing attention and skill performance for the effectiveness of the shot put among the students of the Faculty of Physical Education at Yarmouk University. Methods: The researcher used the experimental method in the manner of the two equal groups. The study sample consisted of (36) students from the Faculty of Physical Education who were registered for the course of teaching athletics in the summer semester of the academic year 2020/2021. They were chosen in a deliberate way, they were divided into two equal groups with (18) students for each group. the experimental group applied the educational program using the problem-solving strategy, while the control group applied the curriculum for the effectiveness of the shot put in the usual lecture method. Skills for the effectiveness of the shot put the researcher designed a special form for this purpose. Results: The results of the study showed the effectiveness of teaching using the problem-solving strategy on focusing attention and skill performance of the effectiveness of the shot put among students of the Faculty of Physical Education at Yarmouk University, and that there were differences in the dimensional measurements between the members of the experimental and control groups in the concentration of attention and skill performance of the effectiveness of the shot put and in favor of the experimental group. Conclusions: The study recommended the necessity of paying attention to using problem solving strategy to focus attention and skill performance for the effectiveness of the shot put.